Descriptive Analysis of the Efficiency of Vat Period Tax Return (SPT Masa PPN) Reporting Before and After the Full Implementation of the Coretax System at PT Jasa Citra Lestari - Fitri Handayani; Latersia Br Gurusinga; Kennie Khoshashi (SEAN Institute, 2026)
This study aims to determine the effect of the efficiency of VAT Periodic Tax Return (SPT Masa PPN) reporting before and after the full implementation of the Coretax system at PT Jasa Citra Lestari. The research method used is a quantitative approach, with PT Jasa Citra Lestari as the object of the study. Data analysis was conducted through stages of data coding and reduction, data display, as well as conclusion drawing and verification. The results show that prior to the implementation of the Coretax system, VAT reporting was carried out using separate systems such as e-Faktur and webfaktur, and frequently encountered technical issues such as system errors and slow servers, resulting in longer processing time and inefficiency. After the implementation of Coretax, the reporting process became simpler and more integrated within a single system, supported by automation and validation features that accelerate the process, reduce errors, and improve data accuracy, making it more efficient and effective. Therefore, there is a significant difference in efficiency before and after Coretax implementation, indicated by time savings, reduced workload, and improved reporting quality.